Development Of A Modified Bandage Backpack For Patients With Clavicle Fracture - Perdana, Wahyu Putra; Anam, Agus Khoirul; Abiddin, Andi Hayyun (Health Access Journal, 2026)
Clavicle fractures often occurred at the center due to lack of muscle and ligament protection. Management of clavicle fractures could be done operatively or non-operatively, with arm slings being the most common tool. However, arm slings tended to be less stable, so bandage backpacks were developed as an alternative. Although more stable in fixation, bandage backpacks still had weaknesses that required the development of new designs that were more comfortable and safe. This study aimed to develop a modified bandage backpack product for patients with clavicle fractures. This research used the Research and Development (R&D) method. The research procedure used the ADDIE model consisting of 5 stages including analysis, design, development, implementation, and evaluation stages. Product validation was carried out by four media experts consisting of 2 nursing lecturers and 2 emergency room nurses who were members of BAPENA PPNI Blitar City. Results from expert validators showed a feasibility score of 92%. The results of this modified bandage backpack product assessment met the criteria as very feasible with some suggestions and input. The modified bandage backpack product was expected to be used as an alternative treatment for patients with clavicle fractures